Multiple FNH-Like Lesions in a Patient with Chronic Budd-Chiari Syndrome: Gd-EOB-Enhanced MRI and BR1 CEUS Findings. (11th March 2012) - Newerla, Caroline; Schaeffer, Fabienne; Terracciano, Luigi; Hohmann, Joachim
Abstract : A-26-year old female patient with chronic Budd-Chiari syndrome due to different underlying blood disorders applied for a two-year followup of the liver with Gadolinium-ethoxybenzyl-diethylenetriaminepentaacetic-acid-(Gd-EOB-DTPA-) enhanced MRI. The liver function tests were raised. Besides showing a progressive hepatosplenomegaly and a cirrhotic liver alteration, the MRI revealed multiple new nodular lesions in all liver segments. These lesions showed typical patterns in the precontrast images, while there was an arterial and a persistent portal venous enhancement. In the hepatobiliary liver-specific late phase, a central "washout" and a persistent rim enhancement were observed (target sign). The additionally performed contrast-enhanced ultrasonography showed a strong zentrifugal arterial enhancement of the lesions followed by an isoechoic enhancement in the portal venous and delayed liver phase. Histologically these lesions turned out as focal nodular hyperplasias (FNH) or FNH-like lesions, also known as large regenerative nodules (LRNs). Differentiation between regenerative nodules like LRN and hepatocellular carcinoma (HCC) in cirrhotic livers is crucial, and the target sign in the hepatobiliary phase of Gd-EOB-DTPA as well as the centrifugal arterial enhancement followed by an isoenhancement during a CEUS might be useful for establishing the correct diagnosis of such hypervascular lesions with proliferated and likely aberrant bile ducts.